Plan de orientación vocacional y profesional para la elección de la carrera universitaria de los estudiantes del tercer año de bachillerato, paralelo a de la unidad educativa dr. Manuel Cabrera 2018-2019. - Jarro Morocho, Carolina Marisol (2020)
The present research entitled Vocational and professional orientation plan for the choice of university career for students in the third year of high school, parallel A of the Dr. Manuel Cabrera Educational Unit 2018-2019, being the general objective: To develop the vocational and professional orientation plan for the choice of university career. Quantitative approach of descriptive character, of cross section, quasi-experimental design; based on scientific, deductive, inductive, analytical, synthetic, historical logical and statistical methods. A survey of a sample of 22 students was used, which has been statistically and analytically processed. According to the results obtained in the pre-test, those investigated lack knowledge about vocational and professional orientation; as for personal or internal factors, students do not identify personal tastes, as well as potential aptitudes or abilities to perform in a given field, this process of internal inquiry that is fundamental at the time of choice; It is also evident that students do not manage to identify the external factors that are the environment in which the student develops, made up of certain family, social and economic structures that constitute the scenario from which the student positions himself when facing his career choice. After the application of the post-test vocational and professional orientation plan, significant changes are evident in those investigated, with high levels of knowledge about vocational and professional orientation and the internal factors that influence the choice, such as personality, aptitudes, professional interests, as well as in relation to the external factors, considering the economic factor and the academic offer with relevant aspects to consider when choosing a profession. Concluding the results of the first diagnosis they did not achieve knowledge of the vocational orientation nor their decision to choose the university career, of the later diagnosis made it is evident the effect of the Vocational and Professional Orientation in the career choice, they changed criteria allowing to affirm that the results validate the proposal of the Plan of Vocational and Professional Orientation, that at the moment of their entrance to the workshop some students do not have enough information for the choice of career, after the intervention through the Pearson's linear correlation coefficient, they reach an average positive correlation, these data allow to affirm that the results validate the Vocational and Professional Orientation Plan and it is quite significant in the internal and external factors as aspects that influence the vocation and the choice.